A territorialização do agronegócio do milho no médio sertão sergipano : novas configurações espaciais e produtivas - Silva, Paulo Adriano Santos (2022)
Under the aegis of agribusiness, the production of transgenic corn has territorially expanded in Sergipe, driven by the systematic action of the State in the dissemination of credit policies and in encouraging the use of technological packages. The expansion of this model of corn production, based on the logic of the commodity market, has accelerated the process of territorialization of monopoly capital in the countryside, and, therefore, amplified contradictions and impacts of an economic, productive and socio-environmental bias. That being so, the aim of this research is to analyze the process of territorialization of the corn agribusiness and the constitution of new configurations in the productive dynamics of agriculture, having as research locus the Territory of the Middle Bushlands of Sergipe. To achieve this goal, a quantitative-qualitative approach was used, supported by the following methodological procedures: bibliographic survey; documentary research; fieldwork; systematization and analysis of primary and secondary data; and reflection of the results. In addition, during the empirical research, the “snowball” technique, created by Bailey (1994), was adopted to facilitate the process of identifying research subjects. In view of this, it was found that the resurgence of corn production is a reflection of a structural macro-project of agribusiness, which was territorialized in this area in order to increase capital and feed back other productive sectors, such as the poultry and industrial sector. Based on a commodity model, agribusiness has laid ground for the entry of agro-industrial and financial capital into this territory. If, on the one hand, the construction of corn production led to an exponential increase in productivity rates, on the other hand, it also caused the loss of productive autonomy, with the increase in dependence on technological packages, the expansion of deforestation and the risks of contamination and intoxication by the indiscriminate use of pesticides. In addition to environmental problems, the territorialization of the corn agribusiness triggered processes of destitution of social, cultural and productive values, once present in the eating habits and way of life of the bushland people. In view of this, it was concluded that all political, ideological and economic construction, orchestrated by the State, in its different instances and organizations, were instituted with the aim of putting forward the production of this commodity, and, therefore, increasing the capital gain of monopoly companies that operate in the territory of Sergipe's Middle Bushland.